ANALYSIS AND EVALUATION OF FISCAL POLICY IN LATVIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The choice and topicality of the research topic is based on the fact that upon strengthening of the government's regulating role in economy, the notion of public finances positions itself, and state budget has become an important subject of both economic and political discussions as implementation of fiscal policy is takes place through it. In order to evaluate fiscal policy, it is necessary to evaluate the potential influence of different fiscal policy instruments on social and economic situation in the state. Aim of the research – to evaluate activities of fiscal policy implemented in Latvia in context of certain tax, namely, influence of corporate income tax on state's economic and financial indicators, identifying the main risks and imperfections of fiscal policy when ensuring state's budget. Applying simulation methods in the environment of Matlab/Simulink, the authors analyze and evaluate the influence of fiscal decisions and their implementation on the situation in Latvia, analyzing the most important tendencies in the sphere of corporate income tax payments according to the tax reform commenced in 2018.